Issues and challengers in environmental management in Malaysia - Jamaluddin Md. Jahi, (Environmental Management Society, Malaysia, 2002)
It is a well-known fact that there is interaction between various components of the environment. The atmosphere, the lithosphere and the biosphere are inter-dependent of each other in a symbiotic manner. One component cannot function without the others. The inter-relationship between the various components is vital in the achievement of a dynamic equilibrium condition in the environment. The absence or extended disturbance of one component may render dynamic equilibrium unattainable and leads to environmental degradation. The exploitation of natural resources and other improperly planned and inadequately controlled development activities often lead to environmental degradation. In this country, there is a sure sign of environmental degradation even before the achievement of independence in 1957 which is manifested in various problems of pollution either in air, water or on land. Deforestation, mining, land and infrastructure development has not only led to soil erosion, sedimentation of drainage system, but also more frequent and intensified flood and flash flood occurrences. Agriculture, especially livestock rearing, and industrial activities have been contributing to water pollution that affect not only aquatic life and recreational activities, but also water treatment plants for domestic water supply. Motor vehicles and industrial activities also pollute the atmosphere, especially in urban-industrial areas. The recurrent occurrence of haze episodes since early 1980’s is another manifestation of environmental degradation that requires effective environmental management plans and strategies. Experience has shown that environmental management through legislative measures alone is not enough to manage the environment. It is suggested that the environment should be managed holistically and in an integrated manner taking into consideration of non-legislative measures